HUBUNGAN FAKTOR INTERNAL PENDERITA TB TERHADAP KEPATUHAN PENGOBATAN TB - Unok, Warihan; Rahmah, Lestari; Mahendika, Devin; Mudhofar, Muhamad Nor (Ensiklopedia of Journal, 2025)
Abstract: The high number of Tb cases is inseparable from the compliance of Tb sufferers in the treatment process. Based on a preliminary study conducted at Puskesmas Pacar Keling during the period January to June 2023, there were 37 patients suffering from tuberculosis (TB). From the results of interviews with 5 respondents, it was found that 3 of them showed compliance in undergoing TB treatment, while the other 2 were not compliant with the recommended treatment. The purpose of the study was to determine the relationship between internal factors of Tb patients and Tb treatment adherence. The research design used in this study was cross sectional. The research was conducted in the Working Area of Pacar Keling Health Center. The research was conducted in November 2023. The population in this study were all pulmonary TB patients at the Pacar Keling Surabaya Health Center from January 2023 to June 2023, totaling 37 patients. The sample amounted to 34 respondents. The sampling technique used probability sampling with Simple Random Sampling technique. The research instrument used a research questionnaire. Data analysis was performed univariate and bivariate. The results showed that there was a relationship between the level of knowledge (p value: 0.000) and motivation (p value: 0.004) with Tb treatment compliance. It is recommended that respondents remain disciplined and regular in undergoing treatment and taking OAT until declared cured by health workers.Keywords: Compliance, Health Center, Tuberculosis.